The Environmental Radiation Pollution in Urban Buildings - Al Smadi, Wajih Basem (2015)
Indoor environmental quality is essential in urban buildings. Health of occupants depends greatly on factors related to air quality and space maintenance. However, a new form of pollution has emerged in developed nations due to the excessive use of electric and electronic products. This pollution is caused by the unavoidable emanation of electromagnetic fields in the free air and space penetrating the living organisms and causing adverse health effects over the long term. The design and construction studies do not sufficiently account for the radiation-intoxication issues within the indoor environments due to the lack of awareness on the importance of the electromagnetic radiation field. This dissertation reviews the latest literature on the indoor environmental radiation and its health implications. The research experimental study gives an overview on simple procedures to measure, identify and discuss the RF radiation in two residential apartments. Results of this study are compared to the international standards on exposure limits and addressed accordingly in the analysis. The findings discussion and research outcomes should urge project planners to initiate guidelines and recommendations in order to mitigate radio-frequency fields in indoor environments throughout the design phases. The end-users should also be capable of using measurement methodologies to perform a preliminary assessment of the radiation exposure level at their own premises.